A PHONOLOGICAL ANALYSIS ON MADURESE ENGLISH STUDENTS’ PRONUNCIATION IN READING AN ENGLISH TEXT - Saputri, Tiyas (Universitas Nahdatul Ulama Surabaya, 2016)
The study focuses on the analysis of phonology on Madurese English students‟ pronunciation in reading an English text. The writer identified kinds of English oscillographic pronunciation made by Madurese students in reading an English text, the differences of English oscillographic pronunciation between Madurese students and that of the English native speaker in reading an English text and how Madurese language characteristics influences Madurese English students‟ pronunciation. To collect the data, she observed and recorded the Madurese English students‟ pronunciation by using MP4 then analysed it descriptively by using Praat program version 4027. Then, she found that the oscillographic pronunciation of Subject 2 and Subject 3 when it is compared to subject 1 is different and makes different meaning, but sometimes not. Furthermore, it is found that Madurese language characteristics influence them in reading the English text. Therefore, they made some sound changes: vowel, consonant and diphthong. Moreover, they also made deletion and addition. She concludes that their pronunciation is unintelligible because they often make mispronunciation.